Fewer spine degenerations among Southeast Asians than among Southern Chinese suggests populations from a warmer climate have inherently better spine health - Tang, Sheng-Nan; Li, Cai-Ying; Leung, Jason C S; Kwok, Anthony W L; Kwok, Timothy C Y; Wáng, Yì Xiáng J (Quantitative imaging in medicine and surgery, 2024)
Compared with older Caucasians, older Chinese have remarkably lower prevalence and lower severity of spine degenerative changes. There have been few studies on Southeast East populations. This study aims to compare radiographic spine degeneration features among older Hong Kong (HK) Chinese, older Thais, and older Indonesians. This study included 195 Thai women (mean: 73.6 years), 202 Thai men (mean: 73.7 years), 227 Indonesian women (mean: 70.5 years), and 174 Indonesian men (mean: 70.2 years), as well as same number of gender- and age-matched HK Chinese. The recruitment plan was that the participants would represent the general older population of their respective communities. With spine radiograph, spine hyper-kyphosis, osteoarthritic wedging (OAw), acquired short vertebrae (SVa), general osteophyte formation, lumbar disc space narrowing, and lumbar spondylolisthesis were assessed. Compared with Southeast Asians (Thais and Indonesian data together), Chinese women and men had a higher prevalence of hyper-kyphosis (24.9% 16.4%), OAw (2.4% 0.9%), general osteophyte formation (15.3% 10.5%), lumber disc space narrowing (27.6% 20.3%), and lumbar spondylolisthesis (20.7% 15.3%). The trends were also consistent for sub-group data analyses. An even lower prevalence was noted among Indonesian women and men than among Thais in general osteophyte formation (5.9% 14.1%), lumbar disc space narrowing (18.3% 24.1%), and lumbar spondylolisthesis (11.4% 19.3%). This study showed a lower prevalence of spine degeneration changes among older Thais and older Indonesians than among older Chinese. Indonesians, who inhabit an even warmer climate, show even fewer spine degeneration changes than Thais.